Inventory Control Models with Motivational Policies - Taleizadeh, Ata Allah (Springer International Publishing, 2018)
This book examines the different motivational policies used for inventory management. In many competitive markets, sellers use motivational policies to encourage the customers to buy more and these kinds of strategies are used as competitive tools. This book brings together all the motivational policies for lot sizing decisions and offers a useful guide for inventory control. Each chapter applies deterministic inventory models such as economic order quantity (EOQ) and economic production quantity (EPQ), but also stochastic models for the motivational policy covered. The book begins exploring quantity discounts such as all-unit and incremental discounts. It then looks at delayed payment or trade credit policies that are applied by many suppliers and/or wholesalers to increase their sales. The motivational policies covered in the following chapters are dedicated to advance payment/prepayment schemes and also special sales offered by retailers to increase sales levels or decrease the inventory level. Finally the book concludes with a review of announced price increases, which persuades customers to buy a product at the current price, rather than paying more for it in the future. Inventory Control Models with Motivational Policies should be useful for professionals working on supply chains, but also researchers in operations research and inventory management.